Zusammenarbeit von Einrichtungen: Eine theoretische Perspektive für die Forschung zum Lebenslangen Lernen - Ewa Przybylska (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2017)
The cooperation between institutions remains the traditional topic of adult education. Nowadays, it is gaining new interest among researchers as the popularity of lifelong learning is growing. The cooperation between institutions arises potential which should be used to shape optimal conditions for life-long learning of the society. The article defines the main concepts relating to the cooperation with different social partners. It presents the goals, functions and profits achieved through joint action. Even though some institutions share doubts concerning the cooperation with other organizations on local or regional level, it is essential to notice that cooperation is generally profitable for all involved partners and serves the local community.